(untitled) (International Journal of Engineering and Computer Science, 2014)
As the scale of integration keeps growing, more and more sophisticated signal processing systems are being implemented on a VLSI chip. These signal processing applications not only demand great computation capacity but also consume considerable amounts of energy. While performance and area remain to be two major design goals, power consumption has become a critical concern in today’s VLSI system design. Multiplication is a fundamental operation in most arithmetic computing systems. Multipliers have large area, long latency and consume considerable power. Previous work on low-power multipliers focuses on low-level optimizations and has not considered well the arithmetic computation features and application-specific data characteristics. Binary multiplier is an integral part of the arithmetic logic unit (ALU) subsystem found in many processors. Booth’s algorithm and others like Wallace-Tree suggest techniques for multiplying signed numbers that works equally well for both negative and positive multipliers. This synopsis proposes the design and implementation of Booth multiplier using VHDL . This compares the power consumption and delay of radix 2 and modified radix 4 Booth multipliers. The modified radix 4 Booth multiplier has reduced power consumption than the conventional radix 2 Booth Multiplier.